Venous Thromboembolism in Pediatric Inflammatory Bowel Disease: A Case-Control Study. Issue 5 (16th May 2021) - Mitchel, Elana B.; Rosenbaum, Sara; Gaeta, Christopher; Huang, Jing; Raffini, Leslie J.; Baldassano, Robert N.; Denburg, Michelle R.; Albenberg, Lindsey
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: Inflammatory bowel disease (IBD) is associated with increased risk of venous thromboembolism (VTE). Despite this recognized risk, there are limited data and no anticoagulation guidelines for hospitalized pediatric IBD patients. The objectives of this study were to characterize pediatric IBD patients with VTE and determine risk factors. Methods: This was a nested case-control study comparing hospitalized children with IBD diagnosed with VTE to those without VTE over a decade at a large referral center. Standard descriptive statistics were used to describe the VTE group. Multivariable conditional logistic regression was used to assess risk factors. Results: Twenty-three cases were identified. Central venous catheter (CVC) presence (odds ratio [OR] 77.9; 95% confidence interval [CI]: 6.9--880.6; P  < 0.001) and steroid use (OR 12.7; 95% CI: 1.3--126.4; P  = 0.012) were independent risk factors. Median age at VTE was 17 years (interquartile range [IQR] 13.5--18.2), and in 48%, VTE was the indication for admission. Median duration of anticoagulation was 3.8 months (IQR 2.3--7.6), and there were no major bleeding events for patients on anticoagulation. There were no patients with known sequelae from VTE, though 22% had severe VTE that required interventions. Conclusions: Pediatric patients with IBD are at risk for VTE, although the absolute risk remains relatively low. The safety and efficacy of pharmacologic thromboprophylaxis needs to be further evaluated in this population with attention to risk factors, such as steroid use and presence of CVC.